Intermittent Abdominal Pressure Ventilation: An Alternative for Respiratory Support. (23rd August 2021) - Fiorentino, Giuseppe; Annunziata, Anna; Coppola, Antonietta; Marotta, Antonella; Simioli, Francesca; Imitazione, Pasquale; Lanza, Maurizia; Cauteruccio, Rosa; Esquinas, Antonio M.
Abstract : Intermittent abdominal pressure ventilation is a positive pressure ventilation technique that works with abdominal compressions. It has been known since 1938; however, for many years, it was out of production. In recent years, a new device has been produced that has captured the attention to this old respiratory support technique. We considered eight patients with respiratory failure secondary to a neuromuscular disease (congenital myopathy, Duchenne dystrophy, and amyotrophic lateral sclerosis) intolerant to daytime noninvasive ventilation (NIV). IAPV was proposed as an alternative to NIV. We performed baseline and post-IAPV respiratory function assessment. All patients, two years later, are still using intermittent abdominal ventilation. Intermittent positive abdominal mechanical ventilation can be a valid alternative to noninvasive mechanical ventilation with a nasal or face mask. It improves gas exchange, symptoms, and quality of life, decreases the incidence of pneumonia, and can avert the need for intubation and tracheotomy.